Redes de comunicação no coletivo Dulcineia Catadora e o arte ativismo do convívio - Braga, Ana Cristina D´Angelo (2014)
This research chooses creative actions from artistic collective Dulcineia Catadora and tracks the poetic path chosen by the group in its activist art practical. The actions of this collective as activist art are developed over time from the aesthetics of conviviality: instant and temporary memberships form and transform the sensible route of the group through collaborative actions that favor the encounter above the possible final work. The research also makes references to the origin of the Argentine Cartonero model and the scattering of this practice in Latin America and other continents. The research aims to develop theoretical framework for understanding the collective and networked practices, clarifying their communicational characteristics, taking into account reflections and the reconfiguration of the tripod art/work/policy. For theoretical reflection on choices and actions of the group the criticism of process method was used, with emphasis on the pursuit of connections established by the poetic project through its tracks and actions. Thinking creation as network directs the reading of signs and communicational procedures of the artistic collective and establishes genuine questions to deal with the moving process. Especially in a poetic project with hybrid languages the theory of creation is adopted as semiotic process (trend, material rewards, fallibility, chance, input of new ideas, lack of hierarchy , infinite regression and progression and communication) to establish the sensible and intellectual route. The following traces of actions were selected from the creative and poetic journey of Dulcinea Catadora established over the last five years: Records in the collective blog (Dulcinea Catadora), videos (Dulcinea and Paul Bruscky and the video that records the creating process of the books to the Art Museum of Rio), book releases, participation in events and the routine of cartonero books manufacturing workshops in São Paulo, Rio de Janeiro and Buenos Aires